The mechanics of automated trade execution systems - Domowitz, Ian (Journal of Financial Intermediation, 1990)
The algorithms of three automated trade execution systems are compared with respect to price discovery and quantity determination in markets for futures, options, and stocks. Efficiency of these systems is measured using the classical benchmark of Walrasian equilibrium pricing; welfare is measured in terms of trader and customer surplus. Floor trading is analyzed similarly and provides another benchmark for comparison of system performance. Journal of Economic Literature Classification Number: 314.